Does the use of contraceptives endanger the life of the conceived child? - Prusak, Małgorzata (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Studies indicate that hormonal contraceptives and intrauterine devices do not completely inhibit ovarian activity, so conception remains possible during use, confirmed by pregnancy rates up to 7% among combined-pill users. The chapter examines the mechanisms behind this incomplete suppression and resulting anti-implantation effects.Incomplete inhibition partly results from hormone doses reduced to limit harm to the woman. These agents combine a contraceptive effect, via ovulation inhibition and impaired sperm quality, with an anti-implantation effect via effects on embryo transport and the endometrium, more likely with low-dose gestagens and devices inhibiting ovulation less. Levonorgestrel pills may fail to destroy the embryo more often than assumed; ulipristal near ovulation likely acts as an early abortifacient.Hormonal contraceptives and intrauterine devices may thus contribute to early miscarriage, a fact users should be informed of.